LCN2 as a Potential Diagnostic Biomarker for Ulcerative Colitis-Associated Carcinogenesis Related to Disease Duration - Kou, Fushun; Cheng, Yuan; Shi, Lei; Liu, Jiajing; Liu, Yuyue; Shi, Rui; Peng, Guiying; Li, Junxiang (Frontiers in Oncology, 2022)
Background: Patients with long-duration ulcerative colitis (UC) had a higher risk of developing ulcerative colitis-associated carcinogenesis (UCAC) when compared to those with short-duration. This study aimed to discover the biomarker for cancer surveillance related with disease duration. Methods: The microarrays were divided into short-duration (<10 years) of UC, long-duration (≥10 years) of UC, UCAC and normal groups in the gene expression omnibus (GEO) datasets. Differentially expressed genes (DEGs) of GEO and the hub genes of the selected Weighted Gene Co-expression Network Analysis (WGCNA) were intersected to obtain the overlapping genes. Among these genes, the key gene was identified by using the protein-protein interaction (PPI) network, Gene Ontology (GO), KEGG analysis, the CytoHubba of Cytoscape and the expression levels. Also immunofluorescence of human colonic mucosa and animal experiment were used to validate the expression trend of key gene in the progress of UC developing into UCAC. Results: LCN2 was more relevant with disease duration of UC and significantly negative correlated with risk of UCAC. The expression level of LCN2 in short-duration was higher than that of long-duration (P<0.01), long-duration was higher than that of UCAC (P=0.001), and UC and UCAC were all higher than that of the normal (P<0.001). We then discovered that expression trend of LCN2 in blood and stool samples was consistent with that in colorectal mucosa. Conclusion: The research indicates that LCN2 could be a novel biomarker to evaluate cancer surveillance related with disease duration of developing UC into UCAC. Compared with that of blood samples, stool detection of LCN2 may have more advantages for diagnosis value of early stage of UCAC as a compliment to colonoscopy surveillance.